Implementing Intensive Interaction in a specialist school setting - Sparling, Wendy (2020)
This study evaluates the process of implementing a new teaching approach, in this case Intensive Interaction, into a specialist school. The aim of the project was to improve engagement with pupils with autism, severe learning difficulties and challenging behaviour in education. This study was framed by the transactional model of child development (Wetherby and Prizant, 2000), the social model of disability (Corker and Shakespeare, 2006) and Lewin’s model of change management (1947) as well as inter-subjectivity theory. During a fourteen-week data collection period, practitioners’ ability to implement the approach and sustain the change was evaluated. The receptiveness of staff to the training was also investigated. Videos recordings of three dyad pairs of pupil and practitioner generated a large volume of rich qualitative data. The existing educational approach was video recorded weekly over a period of six weeks and this was followed by staff training on Intensive Interaction. Post-training educational practice was recorded weekly and the video recordings provided the basis for both video stimulated recall sessions and a warm and cool feedback session to increase the capacity for staff to reflect critically on their own practice. In addition to the video and stimulated recall process, questionnaires were utilised to gain the views of the wider staff team about the training and the implementation of Intensive Interaction. The data from the questionnaires produced quantitative data that was used to triangulate some of the findings from the video study. Despite the commonality of the training and similar challenges faced by each pupil, the study demonstrated significant variances in the implementation. The analysis highlights the factors that influence the implementation in this case and have led to the development of a “Ladder of Intensive Interaction Techniques” which can guide the progressive development of the practitioner’s skills in II. A second model was also developed “Stages of Professional Development” and this focuses on the professional development process more generally to allow a potentially wider application with similar interventions in specialist contexts. The research shows how such specialist training programmes are unlikely to be uniformly effective as practitioners’ layer and blend new ideas onto existing beliefs, knowledge and practice. There are clear implications for school leaders and other change agents.